Sistem Informasi Layanan Pemerintahan Desa Sawangan Grinsing Batang Berbasis Web - Siska Ginting; Yulia Kurniawati (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2022)
Sawangan village, Grinsing sub-district, Batang district is the village government in charge of regulating the interests of the local community assisted by village officials. Sawangan village has a population of 6,497 people with 3,272 women and 3,225 men. Sawangan village apparatus had difficulties in managing the community's interest in the village, such as arranging for an introduction to the making of Identity Cards, Family Cards, death certificates and other application letters that required village information. It is necessary to create an online web-based village service information system in order to manage all the needs of the sawangan village community. The system is made using the Waterfall development method which works systematically and gradually. The online web-based village service information system is tested using blackbox testing which produces system features that suit user needs.